Desert Duty : On the Line with the U.S. Border Patrol - Broyles, Bill, 1944 July 9-; Haynes, Mark (Mark H.) (Book collections on Project MUSE., 2010)
"While politicians and pundits endlessly debate immigration policy, U.S. Border Patrol agents put their lives on the line to enforce immigration law. In a day's work, agents may catch a load of narcotics, apprehend groups of people entering the country illegally, and intercept a potential terrorist. Their days often include rescuing aliens from death by thirst or murder by border bandits, preventing neighborhood assaults and burglaries, and administering first aid to accident victims, and may involve delivering an untimely baby or helping stranded motorists. The book features interviews with nineteen active-duty and retired agents who have worked at the Wellton, Arizona, station that watches over what is arguably the most perilous crossing along the border--a sparsely populated region of the Sonoran Desert with little water and summer temperatures that routinely top 110°F. The agents candidly discuss the rewards and frustrations of holding the line against illegal immigrants, smugglers, and other criminal--while often having to help the very people they are trying to thwart when they get into trouble in the desert."